Measurement of Service Quality and Customer Satisfaction Level Marketplace in Bekasi with Fuzzy Servqual Method - Wiwiek Widyastuty; Moch Abdul Azis; Muhammad Hasan (Institute of Computer Science (IOCS), 2021)
The increasing number of internet users in Indonesia encourages business actors (traders, distributors, producers) and consumers to choose to conduct buying and selling transactions of goods or services online. This is one of the factors starting the number of online businesses in Indonesia. Starting from online shops, e-commerce, and marketplaces. Marketplace is a place for transactions (between business actors and consumers). The number of marketplace business actors makes each other try to offer the best products, low prices, and other services with the aim of achieving consumer satisfaction in transactions. This research was conducted to measure the quality of service provided by Marketplace developers to customer satisfaction in Bekasi in particular. The method used is Fuzzy Servqual by measuring based on five dimensions of service quality and with the Customer Satisfaction Index (CSI) to measure customer satisfaction. The five dimensions of service quality show the gap negative relationship between the service received and the service expected. Meanwhile, the Customer Satisfaction Index (CSI) produces a value that can be categorized into a